”Han talte de om som en hjälte” – Performative Masculinity in the TV-series S*M*A*S*H and Pistvakt - Lindkvist, Jonas (Nordlit, 2023)
”Han talte de om som en hjälte” examines the use of parody and satire in the Swedish comedy series S*M*A*S*H (1990) and Pistvakt (1998–2000) as well as the feature film Pistvakt – En albinovästern från de vita vidderna (2005). By analyzing how the series illustrates performative masculinity from the definitions of Judith Butler in Gender Trouble (1990), conclusions on whether they destabilize normative heterosexual masculinity are drawn. S*M*A*S*H shows two normative ideals for masculinity, the finance mogul that the characters fail to reach, and the elite athlete that the characters discard. Pistvakt shows several different normative masculinities, but also destabilizes normative masculinity mainly by illuminating the performativity of the construction of masculinity by making the character Sven-E a parodically unattainable super hero representation of masculinity.